“Pengadilan Warganet” Terhadap Maladministrasi Pelayanan Publik - Mukromin, Ngutsman; Mujib, Mujib; Jumadi, Jumadi (Public Policy and Management Inquiry, 2023)
The research entitled "Netizen Court" against Public Service Maladministration aims to find out how the digital community (netizens) cares about public service maladministration in Indonesia. The method used in this research is the library research method with an analytical descriptive approach, which examines the norms related to maladministration in government actions and then compares them with field data. The data presented in this study are primary in the form of laws and secondary data in the form of articles and news from trusted media. Maladministration actions according to Law No. 37 of 2008 concerning the Ombudsman of the Republic of Indonesia are behavior or actions against the law, exceeding authority, using authority for other purposes than those for which the authority is intended, including negligence or neglect of legal obligations in the implementation of public services carried out by state and government administrators which cause material and/or immaterial losses to the community and individuals. Meanwhile, citizens as accessors and supervisors of public services who have carried out their duties, namely making complaints about maladministration actions according to procedures established by the government, did not get a satisfactory response from the government. Therefore, citizens find their way to express their frustration with maladministration by making trending topics on social media. A particular case that becomes a trending topic on various social media has proven to have a major impact on the quality of public services. Keyword: maladministration, netizens, viral,social media